APPLICATION OF SANCTIONS FOR PERPETRATORS OF PHYSICAL VIOLENCE AGAINST CHILDREN COMMITTED BY PARENTS IN THE JURISDICTION OF THE PEKANBARU CITY POLICE BASED ON LAW NUMBER 35 OF 2014 CONCERNING CHILD PROTECTION - Bangun, Tri Suranta; Harahap, Irawan; Pardede, Rudi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRACT Article 80 paragraph (1) Jo. Paragraph (4) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection Jo. Article 44 paragraph (1) of Law Number 23 of 2004 concerning the Elimination of Domestic Violence Jo. Article 351 paragraph (1) of the Criminal Code Jo. Article 356 paragraph (1) of the Criminal Code, regulates the prohibition and legal sanctions for parents who commit physical violence in the form of ordinary abuse against their children. The research method is sociological legal research, legislative and case approaches; research location Pekanbaru Police; population and samples from relevant sources; data sources are primary, secondary and tertiary; data collection techniques are observation, non-structural interviews and document studies; data analysis is qualitative; conclusion: inductive. The application of sanctions for perpetrators of physical violence against children committed by parents in the jurisdiction of the Pekanbaru Police based on the regulation has been implemented but the results have not been optimal in 2021 to 2023, as evidenced by several perpetrators not being prosecuted because there was peace between the perpetrators and victims. The obstacles are the law enforcement/government factor, the facility/facility factor and the community factor. Third, efforts to overcome these obstacles are Against the law enforcement/government factor, namely increasing the number of investigators; The police increase cooperation and coordination with the Pekanbaru City Social Service (child social workers); The police implement appropriate policies by prioritizing the interests of children (victims). Against the facility/facility factor, namely the local police increase the budget. Against the community factor, namely the victim is accompanied by a child social worker from the Pekanbaru City Social Service and involves the role of the victim's family who knows the condition of the victim and perpetrator in peace efforts; Investigators maximize separate examinations between the perpetrator and the victim; Investigators apply the right techniques in examining the perpetrator; during the examination the child is not confronted with his parents (perpetrators).Keywords: Abuse, Children, Pekanbaru